Randomized, placebo-controlled trials of dichlorphenamide in periodic paralysis. (12th April 2016) - Sansone, Valeria A.; Burge, James; McDermott, Michael P.; Smith, Patty C.; Herr, Barbara; Tawil, Rabi; Pandya, Shree; Kissel, John; Ciafaloni, Emma; Shieh, Perry; Ralph, Jeffrey W.; Amato, Antony; et al.
Abstract : Objective: To determine the short-term and long-term effects of dichlorphenamide (DCP) on attack frequency and quality of life in hyperkalemic (HYP) and hypokalemic (HOP) periodic paralysis. Methods: Two multicenter randomized, double-blind, placebo-controlled trials lasted 9 weeks (Class I evidence), followed by a 1-year extension phase in which all participants received DCP. Forty-four HOP and 21 HYP participants participated. The primary outcome variable was the average number of attacks per week over the final 8 weeks of the double-blind phase. Results: The median attack rate was lower in HOP participants on DCP than in participants on placebo (0.3 vs 2.4, p = 0.02). The 9-week mean change in the Physical Component Summary score of the Short Form–36 was also better in HOP participants receiving DCP (treatment effect = 7.29 points, 95% confidence interval 2.26 to 12.32, p = 0.006). The median attack rate was also lower in HYP participants on DCP (0.9 vs 4.8) than in participants on placebo, but the difference in median attack rate was not significant ( p = 0.10). There were no significant effects of DCP on muscle strength or muscle mass in either trial. The most common adverse events in both trials were paresthesia (47% DCP vs 14% placebo, both trials combined) and confusion (19% DCP vs 7% placebo, both trials combined). Conclusions: DCP is effective in reducing the attack frequency, is safe, and improves quality of life in HOP periodic paralysis. Classification of evidence: These studies provide Class I evidence that DCP significantly reduces attack frequency in HOP but lacked the precision to support either efficacy or lack of efficacy of DCP in HYP.